NHCs Catalyzed Hydrophosphonylation of α-Ketoesters and α-Trifluoromethyl Ketones - Lin He; Zhi-Hua Cai; Ji-Xin Pian; Guang-Fen Du (The Scientific World Journal)
N-Heterocyclic carbenes catalyzed hydrophosphonylation reaction of α-ketoesters and α-trifluoromethyl ketones was developed. Under the catalysis of 10 mol% IPr, α-ketoesters or α-trifluoromethyl ketones reacted with dialkyl phosphites to provide quaternary α-hydroxyphosphonates in good to excellent yield.